Relations Between the Mandibular Canal and I, II and III Angle Classes in Panoramic Radiographs - Falkine,Raisa Zago (Sociedad Chilena de Anatomía, 2014)
To prevent injury to the inferior alveolar nerve during dental procedures, knowledge of its anatomical location and course of the mandibular canal is imperative. The aim of this study was evaluate the location on panoramic radiographs of the mandibular canal in relation to the apices of the permanent mandibular molars and base mandible, and relate the type of mandibular canal with Angle classes I, II and III. We evaluated 748 panoramic radiographs distributed according to sex and occlusal class (Angle I, II and III) of fully dentate individuals, 1851 age group. The radiographs were divided according to Angle classes based on cephalometric tracing, clinical data from the medical records of each individual and the analysis of of the maxillar and mandibular dental arches models. The same individuals had the mandibular canal bilaterally assessed, and classified according to their location relative to the root apices of the mandibular molars and mandible base. Measurements of the distance from the mandibular canal to the apices of the teeth and mandible base were made on the Software ImageLab2000®. The intra-observer reproducibility of measurements on radiographs was assessed using the coefficient of variation (p<0.0001). Data were submitted to Kruskal-Wallis test, on software BioEstat 5.0. There were statistically significant differences (Kruskal-Wallis test, p <0.0001) between the occlusal classes, with the type of mandibular canal. A larger number of canals types 2 and 3 in class III individuals than in others. In conclusion, the location of the mandibular canal presents morphological changes in relation to the apices of the permanent molars, and the mandibular base according to the Angle classes I, II and III.